Impact of occupational unemployment risk on household spending - Christopher D. Cotton; Vaishali Garga; Justin Rohan (Federal Reserve Bank of Boston, 2022)
The life-cycle consumption and permanent income hypotheses predict that if workers face greater likelihood of unemployment in the future that lowers expected future income, they will save more today. In this paper, we test this hypothesis by looking at the expenditure response of workers to the change in unemployment risk measured at the occupational level. We find that occupational unemployment risk does not have a large impact on consumption expenditure. However, despite investigating multiple forms of occupational unemployment risk for multiple expenditure categories in two expenditure surveys (PSID, CEX), we do not obtain narrow confidence intervals for our estimates, so there remains a possibility of a limited impact.
Keywords: E21; E24; J64; 330; unemployment risk; expenditure; life-cycle consumption; permanent income